Relationship of Socio-economic Profile of Gujjars (Pastoralists) with Knowledge and Adoption of Improved Animal Husbandry Practices - R. Jeelani , S. A. Khandi , M. Y. Beig , P. Kumar and M. S. Bhadwal, (Indian Journal of Extension Education, 2014)
Gujjars are one of the major pastoral communities of India. The study was conducted in Jammu district of Jammu andKashmir, with a view to find out the relationship of knowledge level and adoption of Gujjars regarding improved animalhusbandry practices. The data was collected from 120 Gujjar respondents belonging to R.S Pura and Bishnah block ofJammu district with the help of structured interview schedule containing selected dependent and independent variable,through personal interview technique.The independent variables except age, occupation, herd size and land holding werepositively associated with the dependent variables i.e. knowledge and adoption. Age and occupation were negatively andsignificantly related to the knowledge level and adoption. Herd size was negatively and insignificantly related toknowledge level, but significantly associated with adoption. Knowledge level of respondents was negatively andsignificantly related with land holding however it was insignificantly associated with adoption. Education, socialparticipation, mass media exposure, risk orientation and exposure to training were significantly and positively associatedwith both the knowledge level and adoption of respondents. On the other hand, extension contact and economicmotivation were positively and significantly associated with the knowledge level but insignificantly related to theadoption.